2019
DOI: 10.4102/ajod.v8i0.522
|View full text |Cite
|
Sign up to set email alerts
|

Success in Africa: People with disabilities share their stories

Abstract: Background: Whereas most narratives of disability in sub-Saharan Africa stress barriers and exclusion, Africans with disabilities appear to show resilience and some appear to achieve success. In order to promote inclusion in development efforts, there is a need to challenge narratives of failure.Objectives: To gather life histories of people with disabilities in three sub-Saharan African countries (Kenya, Uganda and Sierra Leone) who have achieved economic success in their lives and to analyse factors that exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…She is planning for a career in computer science, one where she intends to use her skills to help blind people in Kenya connect with each other and to advocate for more inclusive policies. Indeed, African master narratives of disability are even more extremely focused on dependency than American master narratives (Shakespeare, Mugeere, Nyariki, & Simbaya, 2019). Layla expressed gratitude for her blindness, saying,
I think my blindness is the best thing that ever happened to me.
…”
Section: Resultsmentioning
confidence: 99%
“…She is planning for a career in computer science, one where she intends to use her skills to help blind people in Kenya connect with each other and to advocate for more inclusive policies. Indeed, African master narratives of disability are even more extremely focused on dependency than American master narratives (Shakespeare, Mugeere, Nyariki, & Simbaya, 2019). Layla expressed gratitude for her blindness, saying,
I think my blindness is the best thing that ever happened to me.
…”
Section: Resultsmentioning
confidence: 99%
“…Disability is about difference. However, the way that it is understood has gone through fundamental conceptual shifts over the past 30-40 years (Shakespeare 2013). Humans have always noticed and responded to sameness and difference in others.…”
Section: Structure Of the Papermentioning
confidence: 99%
“…They may be forced to do work that is difficult for them or be bullied and maltreated (Mizunoya and Mitra 2012). However, those who have been successful by their own definition often mention the specific support of an individual or community resource that enabled them to access education and then work (Shakespeare et al 2019).…”
Section: Disabled People and Workmentioning
confidence: 99%
“…In a comparative study of people with disabilities in Cameroon and India, researchers found that interviewees prioritized family members' medical needs over their own impairments, which they grew to accept or treat with traditional remedies [14]. Even in cases such as people with disabilities in Kenya, Uganda, and Sierra Leone who succeeded in achieving economic independence, strategies revolved around self-advocacy and self-employment rather than community support [15].…”
Section: Obstacles To Rehabilitation Accessmentioning
confidence: 99%